Sperimentazioni di lettura dei cartolari notarili genovesi per lo studio del territorio (secoli XII-XIV) - Ruzzin, Valentina (Scrineum, 2020)
The diachronic study of a portion of the Genoese districtus, conducted entirely on unpublished notarial documentation, provides the starting point for some general considerations on this documentary complex, especially in relation to broad historiographical issues, and also induces some reflections on possible future lines of research.